2016
DOI: 10.1097/scs.0000000000002388
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric Assessment of Upper Airway Effects on Craniofacial Morphology

Abstract: To investigate craniofacial growth deformities in children with upper airway obstruction, this controlled study was performed. Cephalometry is used as a screening test for anatomic abnormalities in patients with obstructive sleep apnea syndrome. Therefore, the current work selected this method to investigate the effect of upper airway obstruction on craniofacial morphology.Patients with upper airway obstruction (104) were compared with 71 controls. Patients with upper airway compromise had mandibular hypoplasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
0
10
0
4
Order By: Relevance
“…Cephalometry is used to screen for anatomical abnormalities in OSAHS patients. Various studies have shown that the pharyngeal dimensions are correlated with both craniofacial skeletal morphology ( Bacon et al, 1988 ; Wang et al, 2014 ; Yu, Fujimoto & Urushibata, 2003 ) and airway obstruction in OSAHS patients ( Ardehali et al, 2016 ), including those with ANB ( Ceylan & Oktay, 1995 ), SNB ( Ardehali et al, 2016 ), and ANS-PNS ( Yu, Fujimoto & Urushibata, 2003 ). It is well-known that significant differences are apparent between NPOSA and POSA in terms of clinical symptoms, and, theoretically, the characteristics of the craniofacial skeleton may play a role in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Cephalometry is used to screen for anatomical abnormalities in OSAHS patients. Various studies have shown that the pharyngeal dimensions are correlated with both craniofacial skeletal morphology ( Bacon et al, 1988 ; Wang et al, 2014 ; Yu, Fujimoto & Urushibata, 2003 ) and airway obstruction in OSAHS patients ( Ardehali et al, 2016 ), including those with ANB ( Ceylan & Oktay, 1995 ), SNB ( Ardehali et al, 2016 ), and ANS-PNS ( Yu, Fujimoto & Urushibata, 2003 ). It is well-known that significant differences are apparent between NPOSA and POSA in terms of clinical symptoms, and, theoretically, the characteristics of the craniofacial skeleton may play a role in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Cephalometry is used to screen for anatomical abnormalities in OSAHS patients. Various studies have shown that the pharyngeal dimensions are correlated with both craniofacial skeletal morphology (Bacon et al 1988;Wang et al 2014;Yu XJ,;Fujimoto K, Urushibata K 2003) and airway obstruction in OSAHS patients (Ardehali et al 2016), including those with ANB (Ceylan & Oktay, 1995), SNB (Ardehali et al 2016), and ANS-PNS (Yu XJ, Fujimoto K & Urushibata K.…”
Section: Discussionmentioning
confidence: 99%
“…Cephalometry is used to screen for anatomical abnormalities in OSAHS patients. Various studies have shown that the pharyngeal dimensions are correlated with both craniofacial skeletal morphology (Bacon et al 1988;Wang et al 2014;Yu XJ,;Fujimoto K, Urushibata K 2003) and airway obstruction in OSAHS patients (Ardehali et al 2016), including those with ANB (Ceylan & Oktay, 1995), SNB (Ardehali et al 2016), and ANS-PNS (Yu XJ, Fujimoto K & Urushibata K. 2003). It is well-known that significant differences are apparent between NPOSA and POSA in terms of clinical symptoms, and, theoretically, the characteristics of the craniofacial skeleton may play a role in this context.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%